Sistem Digitalisasi BRIMEN (BRI Document Management Systems) Pada PT. Bank Rakyat Indonesia Branch Office Genteng Unit Tulungrejo - Desy Adellia Jovanka; Ulfatun Hasanah; Retna Anggitaningsih (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to explore the processes and procedures for archiving and inputting the BRIMEN (BRI Document Management System) system at PT Bank Rakyat Indonesia Branch Office Genteng Unit Tulungrejo. In the era of growing digitalization, it is important for banking institutions to adapt to changes in consumer behavior that want more efficient and responsive services. Digitalization is not just a trend, but a necessity to improve competitiveness and encourage broader socio-economic growth. The BRIMEN system was introduced by BRI headquarters with the aim of simplifying and modernizing customer document management. With this system, customer documents can be stored in digital form, which minimizes the need for large physical storage and allows faster and more structured access. This research also provides a hands-on understanding of the implementation of the BRIMEN system, which is expected to improve operational efficiency and customer experience in transactions. The results show that the BRIMEN system not only facilitates document management, but also prevents loss, damage, and deletion of customer documents. Thus, the implementation of this system is expected to strengthen BRI's position in an increasingly competitive banking industry and meet increasing customer expectations. This research is expected to serve as a reference for other banking institutions in adopting digital technology to improve their services.